2016
DOI: 10.1002/chem.201604659
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Termination Mechanism in Radical Polymerization by Viscosity: Selective Disproportionation in Viscous Media

Abstract: The termination mechanism of radical polymerization, that is, disproportionation (Disp) versus combination (Comb), determines the chain length and end-group structure of the resulting polymer as well as polymer properties, and yet factors governing the mechanism are still unclear. Furthermore, no attempts have been made to control the mechanism. Here, the effects of temperature and viscosity on the termination of methyl methacrylate (MMA) and styrene (St) polymerization were elucidated by using small molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 31 publications
2
43
2
Order By: Relevance
“…[18,19] They reacted with each other,y ielding the Disp products 9c and 10 c and/ort he Comb product 11 c (Scheme 2, path Ai llustrating the case of methyl methacrylate (MMA) termination). [17] In contrast, Matyjaszewski and Poli have proposed that the tellanyl-radical-mediated chain-transfer pathway is responsible for the formation of Disp products in our study from the mar-ginal Disp/Comb selectivity on the viscosity by using V-601. [16] 2) The termination of methacrylate and styrene polymerizations are significantly changed by the viscosity of the reaction media, and selective Disp was observedi nh ighly viscous media in both cases.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…[18,19] They reacted with each other,y ielding the Disp products 9c and 10 c and/ort he Comb product 11 c (Scheme 2, path Ai llustrating the case of methyl methacrylate (MMA) termination). [17] In contrast, Matyjaszewski and Poli have proposed that the tellanyl-radical-mediated chain-transfer pathway is responsible for the formation of Disp products in our study from the mar-ginal Disp/Comb selectivity on the viscosity by using V-601. [16] 2) The termination of methacrylate and styrene polymerizations are significantly changed by the viscosity of the reaction media, and selective Disp was observedi nh ighly viscous media in both cases.…”
contrasting
confidence: 60%
“…[15][16][17] Polymerend radicals, such as 7c,w ith controlled molecular weight are generated from the corresponding "living" polymer having the organotellurium end group 8c. [15][16][17] Polymerend radicals, such as 7c,w ith controlled molecular weight are generated from the corresponding "living" polymer having the organotellurium end group 8c.…”
mentioning
confidence: 99%
“…The obtained results indicate that addition of the comonomers shifted the distributions toward smaller molar masses, showing the influence of the comonomer on the properties of the final polymer. As MMA termination occurs mainly through disproportionation and monomer conversions were high in all cases and were not affected significantly by addition of the cationic comonomers, this fact may be related to increased chain transfer to the cationic comonomers, which can be favored when the lateral group present in the main chain is bulky, making more difficult the approach of the larger comonomer molecules to the reactive centers due to steric hindrance . This can possibly explain, as shown in Figure 15 , why the addition of praziquantel exerted less significant influence on the molar mass distributions of the obtained copolymers.…”
Section: Resultsmentioning
confidence: 90%
“…The % Disp and Comb obtained in all our experiments are collected in the Supporting Information (Table S1) and shown graphically in Figure and Figure S12. Examination of these results shows quite clearly that the temperature and the solvent nature have little effect, if any, on the relative proportions of Disp and Comb, thus questioning the validity of the previously proposed “advanced collision model” …”
Section: Methodsmentioning
confidence: 89%
“…radicals, it was surprising to find that acrylate radicals resulting from a pMA−TePh macroinitiator terminate almost exclusively (99 %) through Disp, in contrast with several other previous and subsequent reports. In the most recent contribution, it was shown that the product distribution depends on the reaction medium, a greater viscosity resulting in an increase of the Disp/Comb ratio. For example, 59 % Disp was observed for the methacrylate unimer model compound Me 2 C(TeMe)CO 2 Me at relatively low viscosity ( η =1.1 mPas), whereas this amount increased significantly to 94 % at η =84 mPas at room temperature.…”
Section: Methodsmentioning
confidence: 99%